LAND PRICE MAPPING OF JABODETABEK, INDONESIA - Adisti Madella Elmanisa; An An Kartiva; Alfaret Fernando; Rama Arianto; Haryo Winarso; Denny Zulkaidi (Geoplanning: Journal of Geomatics and Planning, 2017)
Land provision is one of the biggest challenges for development in urban area. Most of the available urban land will be the object of speculation to be resold at a higher price when the time is right. In Jabodetabek, where the pace of urban development is faster than other parts of Indonesia, the prices of land show an abnormal increase; they seem to rise too fast. This paper discusses the increasing land prices in Jabodetabek area and argues that the increasing land price has encourages the private developer to bank the land in the area. Based on land price survey in Jabodetabek, urban activity is moving to south Jakarta. The highest land prices were found at East Kuningan, Setiabudi, and South Jakarta. By constrast, the lowest prices were observed in Sumur Batu and Cimuning (Bantar Gebang, Bekasi).It can be concluded that the land price increase also triggered land banking practice in Jabodetabek reaching in total approximately 60% of total area of Jakarta.